Concentrations and stable carbon isotope compositions of oxalic acid and related SOA in Beijing before, during, and after the 2014 APEC - J. Wang; G. Wang; J. Gao; H. Wang; Y. Ren; J. Li; B. Zhou; C. Wu; L. Zhang; S. Wang; F. Chai (Atmospheric Chemistry and Physics, 2017)
To ensure good air quality for the 2014 Asia-Pacific Economic Cooperation (APEC) summit, stringent emission controls were implemented in Beijing and its surrounding regions, leading to a significant reduction in PM2.5 loadings. To investigate the impact of the emission controls on aerosol chemistry, high-volume PM2.5 samples were collected in Beijing from 8 October to 24 November 2014 and determined for secondary inorganic aerosols (SIA, i.e., SO42−, NO3−, and NH4+), dicarboxylic acids, keto-carboxylic acid, and α-dicarbonyls, as well as stable carbon isotope composition of oxalic acid (C2). Our results showed that SIA, C2, and related secondary organic aerosols in PM2.5 during APEC were 2–4 times lower than those before APEC, which is firstly ascribed to the strict emission control measures and secondly attributed to the relatively colder and drier conditions during the event that are unfavorable for secondary aerosol production. C2 in the polluted air masses, which mostly occurred before APEC, are abundant and enriched in 13C. On the contrary, C2 in the clean air masses, which mostly occurred during APEC, is much less abundant but still enriched in 13C. In the mixed type of clean and polluted air masses, which mostly occurred after APEC, C2 is lower than that before APEC but higher than that during APEC and enriched in lighter 12C. A comparison on chemical composition of fine particles and δ13C values of C2 in two events that are characterized by high loadings of PM2.5 further showed that after APEC SIA and the total detected organic compounds (TDOC) are much less abundant and fine aerosols are enriched with primary organics and relatively fresh, compared with those before APEC.